Cross-cultural effects of reminiscence therapy on life satisfaction and autobiographical memory of older adults: a pilot study across Mexico and Spain - Rueda Villasán, Alba; Sánchez Cabaco, Antonio; Mejía Ramírez, Manuel Alejandro; Afonso, Rosa Marina; Castillo Riedel, Eduardo (My University, 2023)
Background There are increasing reports on the cognitive and emotional benefts of positive reminiscence therapy in older people. The objective of this study is to assess the diferential improvement of the quality of life for older peo‑ ple in diferent vital situations (three diferent types of aging) and from diferent countries by implementing a positive reminiscence therapy program (REMPOS). Methods The participants were 144 older adults above the age of 65, 77 participants from Spain (45 experimental groups, 32 control groups) and 67 from Mexico (34 experimental groups, 33 control groups). The participants were recruited from nursing and retirement homes. A factorial randomized design with pre–post measurement with three independent variables: country (Mexico, Spain), condition (experimental, control), and types of aging (healthy aging, HA., mild cognitive impairment, MCI., Alzheimer’s disease, AD). The experimental groups received REMPOS therapy and control groups received standard cognitive stimulation program. The quality of life was measured with the Life Satisfaction Inventory for adults (LSI-A) and autobiographical memory test (AMT) before and after REMPOS therapy. Results The REMPOS intervention showed signifcantly higher positive efects than the control condition on the recall of specifc positive memories across countries and types of aging, except for the Spanish MCI group. Life satisfaction in the Alzheimer’s and MCI group only improved with REMPOS in the Mexican sample. Conclusions The REMPOS efects showed generalizable efects across countries, but the cross-cultural diferences shown highlight the necessity of running studies to test those diferential efects.
Alzheimers Research and Teraphy
Keywords: Aging; Cognitive stimulation; Quality of life; Reminiscence; Specifc memory; Campus Tijuana